THE BEHAVIOR OF SOLAR WIND PARAMETERS AND GEOMAGNETIC ACTIVITY INDICES FOR GEOMAGNETICALLY INDUCED CURRENT OBSERVATIONS - Roslan, Umar; N. Mohd, Anuar; A. N. F. Abdullah, din (2018)
The main objective of the current work is to investigate the behavior of space weather parameter as well as geomagnetic activity indices to observe the Geomagnetically Induced Current (GIC). Subsequently, solar wind parameter and geomagnetic activity indic an evidence that GIC formed during quiet days. The result revealed that the solar wind parameter and geomagnetic activity indices reflect the GIC. However, the solar wind parameter gave the best representation on GIC